2014
DOI: 10.3390/ijms151221754
|View full text |Cite
|
Sign up to set email alerts
|

Looking into a Conceptual Framework of ROS–miRNA–Atrial Fibrillation

Abstract: Atrial fibrillation (AF) has been recognized as a major cause of cardiovascular-related morbidity and mortality. MicroRNAs (miRNAs) represent recent additions to the collection of biomolecules involved in arrhythmogenesis. Reactive oxygen species (ROS) have been independently linked to both AF and miRNA regulation. However, no attempts have been made to investigate the possibility of a framework composed of ROS–miRNA–AF that is related to arrhythmia development. Therefore, this review was designed as an attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 151 publications
1
28
0
Order By: Relevance
“…Despite the complex interactions between ROS metabolism and miRNA levels, there seems to be a considerable overlap between ROS‐regulated miRNAs and miRNAs involved in cardiovascular pathologies. For example, a literature survey described that all 12 miRNAs, which have a confirmed role in atrial fibrillation, are modulated by ROS in cardiomyocytes or vascular cells, and target genes involved in electrical and/or structural cardiac remodelling (Lee et al , ). On an experimental level, a global miRNA profiling study in developing hearts showed that SOD1 overexpression could restore all miRNAs significantly altered by maternal pregestational diabetes mellitus, suggesting that oxidative stress might be responsible for dysregulation of miRNAs targeting cardiac development related pathways in offspring of diabetic mothers (Dong et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%
“…Despite the complex interactions between ROS metabolism and miRNA levels, there seems to be a considerable overlap between ROS‐regulated miRNAs and miRNAs involved in cardiovascular pathologies. For example, a literature survey described that all 12 miRNAs, which have a confirmed role in atrial fibrillation, are modulated by ROS in cardiomyocytes or vascular cells, and target genes involved in electrical and/or structural cardiac remodelling (Lee et al , ). On an experimental level, a global miRNA profiling study in developing hearts showed that SOD1 overexpression could restore all miRNAs significantly altered by maternal pregestational diabetes mellitus, suggesting that oxidative stress might be responsible for dysregulation of miRNAs targeting cardiac development related pathways in offspring of diabetic mothers (Dong et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%
“…MiRNAs play an important part in proliferation and apoptosis of cardiomyocytes, and are involved in ROS‐associated processes. H 2 O 2 affects the expression of different miRNAs in different cell types and concentrations . Therefore, we attempted to find a possible connection among ROS, miRNAs, and selenium supply to understand the protective effects of selenium.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for AF, such as aging, obstructive sleep apnea, diabetes, hypertension, dyslipidemia, obesity, cancer, renal dysfunction, and thyroid diseases, which are all accompanied by deleterious oxidative stress, may act synergistically to cause AF [5,15,[39][40][41][42][43][44], whereby the noncoding microRNAs translate cellular stressors, such as reactive oxygen species, into AF pathogenesis [45]. Emerging evidence suggests a significant role of the altered atrial metabolism, phosphorylation of proteins, inflammatory and autoimmune channelopathies, and presence of autoantibodies to the M2-muscarinic and β 1-adrenergic receptors in the pathogenesis of AF [46][47][48][49][50][51][52][53][54].…”
Section: A Short Overview On Afmentioning
confidence: 99%